Characterisation and modeling of a pulsed molecular beam. (17th January 2021) - Lietard, A.; Gallician, G.; Tan, J.; Gaveau, M.-A.; Briant, M.; Soep, B.; Mestdagh, J.-M.; Poisson, L.
Abstract : Standard techniques used in real-time reaction dynamics experiments, namely photoionization by a pulsed laser and velocity imaging are applied to document the time dependent velocity distribution of 2-hydroxypyridine (2-HP) molecules in a pulsed beam where 2-HP is seeded in either helium or argon. The purpose is to identify features which cannot be assigned to a pure free molecular (effusive in the present case) or a pure continuum (supersonic here) flow regime. The beam is generated in a two stage expansion, where the first stage is driven by a pulsed valve. The experimental work is complemented by simulations. Two phenomena retain the attention: (i) a slow return to the effusive flow regime after the valve opening has generated an intense supersonic flow; (ii) development of a shock wave a short time after the valve opening. GRAPHICAL ABSTRACT: